2015 IEEE International Symposium on Technologies for Homeland Security (HST) 2015
DOI: 10.1109/ths.2015.7225317
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the subject-specific effects of pupil dilation on iris recognition in the NIR spectrum

Abstract: Abstract-A recent report from the National Institute of Standards and Technology (NIST) showed that changes in pupil dilation affect the performance of iris recognition algorithms. Hence, there is a need to explore the effects of pupil motion from a biological standpoint. Our work looks at the pupil's response to light, otherwise known as the pupil light reflex (PLR). By modeling the PLR using a nonlinear delay differential equation while considering images acquired in the near infrared (NIR) spectral band, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Their results showed that, when image comparisons are made between the extreme degrees of dilation 1 to the average dilation, bit errors increased by over 10%. Furthermore, from a dilation viewpoint, Gejji et al [11] revisited the work of [12] to abstractly express the effects of dilation in the visible spectrum and the NIR spectrum. Their work showed that, for the case of steady illumination, Pamplona's model to represent the typical pupillary response, can be expressed as…”
Section: A Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Their results showed that, when image comparisons are made between the extreme degrees of dilation 1 to the average dilation, bit errors increased by over 10%. Furthermore, from a dilation viewpoint, Gejji et al [11] revisited the work of [12] to abstractly express the effects of dilation in the visible spectrum and the NIR spectrum. Their work showed that, for the case of steady illumination, Pamplona's model to represent the typical pupillary response, can be expressed as…”
Section: A Related Workmentioning
confidence: 99%
“…Our motivation for this work comes from the literature in [4], [9], [10] and [11] that suggest a need to develop an analytical and universal approach to describe the effects of dilation on iris recognition caused by ambient lighting. The works of [4] and [10] explore this concept from a template perspective; however, this is mainly from an empirical point of view, which is dependent on the technology and data at hand and does not fully consider the physiological effects of the pupil.…”
Section: B Our Motivation and Contributionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gejji, R.S. et al [13] modeled the pupil's response to light by using a nonlinear delay differential equation in the NIR spectral band, which can be used to develop robust iris recognition algorithms. Son, C. et al [14] captured NIR images and visible color images and presented a new NIR dehazing model based on color regularization, which can solve the color distortion and haze degradation problems at the same time.…”
Section: Introductionmentioning
confidence: 99%